Exercise intensity and load during uphill cycling in professional three-week races - Mujika, I.; Padilla, S.; Santisteban, J.; Goiriena, J. J. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
This study evaluated exercise intensity and load during mountain passes in professional road cycling, using competition heart rate (HR). Sixteen world-class cyclists performed a laboratory test to assess maximal power output (Wmax), maximal HR (HRmax), onset of blood lactate accumulation (OBLA), lactate threshold (LT) and a HR-power output relationship. HR was monitored during 68 OFF, 172 FIRST, and 131 SECOND category passes. Passes were also classified as BEGINNING, MIDDLE or END if they were placed in the first, second or final thirds of a stage, respectively. Competition power output was estimated from competition HR, and training impulse (TRIMP) values from HR and climb duration. Results: %HRmax was significantly higher in OFF and FIRST (77±7% in both), than SECOND (74±7%). Estimated power outputs were 322±55, 332±51 and 305±54 W, the latter two being significantly different. Competition HR relative to HROBLA and HRLT were higher in OFF (86±8%, 98±11%) and FIRST (87±7%, 100±11%) than SECOND (83±9, 95±13%). %HRmax was lower in OFF situated in BEGINNING (66±1%) than in MIDDLE (82±5%) and END (77±7%); in FIRST situated in BEGINNING (74±9%) than in MIDDLE (79±5%); and in SECOND situated in BEGINNING (69±9%) compared to END (75±8%). The amount of TRIMP in OFF, FIRST and SECOND were 93±21, 57±23 and 34±15 (P<0.05). Conclusions: %HRmax, time distribution around HROBLA and HRLT, and TRIMP values reflected the physiological demands of different mountain pass categories, which varied depending on their situation within a stage. The knowledge of these demands could be useful for planning pre-competition training strategies.